Ethanol extracts of mango as antioxidants for broiler chicken - Freitas, Ednardo Rodrigues; Borges, Ângela da Silva; Trevisan, Maria Teresa Sales; Watanabe, Pedro Henrique; Cunha, André Luís da; Pereira, Ana Lúcia Fernandes; Abreu, Virgínia Kelly; Nascimento, Germano Augusto Jerônimo do (Pesquisa Agropecuaria Brasileira, 2012)
The objective of this work was to evaluate the effect of the inclusion of ethanol extracts, obtained from mango seed and peel, in the diet of broilers on their performance and on the lipid oxidation of meat. Three hundred and sisty one‑day‑old male chicks of the strain Ross 308 were distributed in a completely randomized design, with six treatments and six replicates of ten birds. Treatments consisted of: diet without antioxidant (control); diet with addition of 200 ppm of the antioxidant butylhydroxytoluene (BHT); diet with 200 or 400 ppm extract of mango peel (ECAS); and diet with 200 or 400 ppm extract of mango seed (ECAR). The addition of BHT or mango extracts did not significantly affect feed intake, weight gain, and feed conversion. The addition of BHT and 400 ppm of ECAR provided low lipid oxidation in fresh meat, measured by thiobarbituric acid reactive substances before storage. Ethanol extract of mango seed, at 200 and 400 ppm dosage, delays lipid oxidation of chicken meat stored for 15 days.